Dynamic modelling of fuel cell system for mobile application using Simulink environment - Ramli, Ahmad Raoof; Ahmad, Arshad; Ibrahim, Norazana; Lee, Hock Weng (Penerbit Universiti Sains Malaysia, 2004)
Nowadays, the increment of the petrol price has been a major problem for the consumers and it will increase more than 4 cent per litter in period of 6 to 12 month. Thus, there are many new energy developments that friendly to the environment have been commercialized to overcome this phenomenon such as solar energy and fuel cells technology. Among these, fuel cell power systems for transportation applications have received increased attention in recent years because of the potential for high fuel efficiency and lower emissions. A fuel cell converts hydrogen and oxygen into water, directly generating electrical energy from chemical energy without being restricted by efficiency limits of the Carnot thermal cycle (Larminie et al., 2000).